Glutamic Acid as Corrosion Inhibitor for Aluminium in Acidic Medium - Ahmed, Zainab W.; Himdan, Takialdin A.; Radhi, Israa M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Corrosion behavior of aluminium in 0.6 mol. dm-3 NaCL solution in acidic medium ( ) was investigated in the absence and presence of different concentrations of amino acid, glutamic acid, as environmentally – friendly corrosion inhibitor over temperature range (293-308)K. The investigation involved electrochemical polarization method using potentiostatic technique and optical microscopy, the inhibition efficiency increased with an increase in inhibitor concentration but decreased with increase in temperature. Results showed that the inhibition occurs through adsorption of the inhibitor molecules on the metal surface and it was found to obey Langmuir adsorption isotherm. Some thermodynamic parameters ( ) and activation energy ( )were calculated to elaborate the mechanism of corrosion inhibition. The polarization measurements indicated that glutamic acid is of mixed type. The surface characteristic of the inhibited and uninhibited metal samples were investigated by optical microscopy.